The effects of the COVID-19 pandemic on the labour markets in the Western Balkans: exploring age and gender differences - Bartlett, Will (Ревија за социјална политика/Journal of Social Policy, 2021)
This paper analyses the impact of the COVID-19 pandemic on the labour markets of the Western Balkans. In 2020, the pandemic brought the recent growth of the region’s economies to an abrupt if temporary halt, and the paper analyses the impact on activity rates and unemployment rates. The analysis reveals that youth and women, and particularly young women, have been the most severely affected by the crisis. In almost all countries the activity rates of young women have fallen by more than male workers or older workers, while female unemployment rates have simultaneously increased, delivering a double setback for gender equality on the labour market. The paper concludes that future labour market policies should prioritise active labour market policies for the affected young women to assist their return to work through female-friendly training programmes and specialised support for job search and other gender-appropriate policy measures. The capacities of the public employment services in the region will need to be improved to implement targeted and effective active employment policies to support the post-COVID recovery.